Analisis Ketersediaan Lahan Pemukiman di Kota Kecamatan Baranti Sidendreng Rappang - Nurliasari Yulis, Dewi; Syafri, Syafri; Idris Taking, Muhammad (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study is to analyze the carrying capacity of the environment for housing development in Baranti District, Sidenreng Rappang Regency. The type of research in this research is qualitative research. The method of analysis in this study is to use a qualitative descriptive analysis using a Likert scale. The results of this study are that the carrying capacity of the environment for housing development in Baranti District, Sidrap Regency is able to accommodate a population of 30,785 people and the environmental carrying capacity for the next 20 years in Baranti District, Sidrap Regency is still able to accommodate residents in the area with a population of 33,932 people in 2041.